NILAI EKONOMI KEGUNAAN WISATA ALAM SITUGUNUNG TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Rezki, Amala; Lidiawati, Ina; Supriono, Bambang (Universitas Nusa Bangsa, 2021)
The Situgunung area has direct usability value as recreation place and natural tourism. This study aims to determine the perception of visitors and the economic value usability on the natural tourism of Situgunung. This research method uses descriptive methods as well as traveling expenses or the Travel Cost Method (TCM). Testing the perception of visitors using validity and reliability tests were analyzed descriptively using a Likert scale and the economic value use was analyzed using the concept of travel cost (TCM). This result of the study indicates the index of visitors’ perceptions of Situgunung Nature Tourism from the beauty is 89,25% very beautiful, the security aspect is 83,5 % very safe, the hygiene aspect is 77,5% very clean, the accessibility aspect is 77,75% very easy, the facility aspect is 74,25% complete. And the economic value of the use of Situgunung Nature Tourism is Rp.49.197.122.816/year, with the average traveling expenses calculated based on the zone or distance from the area from which the visitor came to the tourist location. With the high perception of visitors and the value of economic use of Situgunung Nature Tourism objects, a more professional management is needed without reducing the concept of natural sustainability.